Impact of melphalan day -1 vs day -2 on outcomes after autologous stem cell transplant for multiple myeloma - Merino, Aimee; Shanley, Ryan; Rashid, Faridullah; Langer, Jenna; Dolan, Michelle; Tu, Sarah; Jurdi, Najla El; Rogosheske, John; Hanna, Kirollos; DeFor, Todd; Janakiram, Murali; Weisdorf, Daniel (Frontiers in Immunology, 2024)
Background Melphalan is the most common conditioning regimen used prior to autologous stem cell transplant (ASCT); however, there are varying data on optimal melphalan timing prior to transplant for best safety and efficacy. Historically, ASCT conditioning consisted of melphalan 200 mg/m2 on day 2 (D-2) (48 h prior to ASCT), but many institutions have since adopted a melphalan protocol with administration on day 1 (D-1) (24 h prior to SCT) or split dosing over the 2 days. The optimal timing of melphalan has yet to be determined. Methods In this single-center retrospective study, we analyzed transplant outcomes for patients between March 2011 and September 2020 admitted for high-dose, single-agent melphalan 200 mg/m2 on D-1 vs. D-2. The primary outcomes were time to neutrophil and platelet engraftment. Secondary outcomes include incidence of hospital readmission within 30 days, 2-year progression-free survival, and 2-year overall survival. Results A total of 366 patients were studied (D-2 n = 269 and D-1 n = 97). The incidence of high-risk cytogenetics was similar between the two groups (37% vs. 40%). Median days to absolute neutrophil count engraftment was similar at 11 days in the D-2 and D-1 cohort (n = 269, range 0–14, IQR 11–11 vs. n = 97, range 0–14, IQR 11–12). Median days to platelet engraftment >20,000/mcL was 18 days for D-2 melphalan (range: 0–28, IQR 17–20) versus 19 days for D-1 melphalan (range: 0–32, IQR 17–21). Overall survival at 2 years post-transplant was similar in both cohorts (94%; p = 0.76), and PFS was 70% in D-2 compared with 78% in D-1 (p = 0.15). In a multivariable model including age and performance status, hospital readmission within 30 days of transplant was higher in the D-1 cohort (odds ratio 1.9; p = 0.01). Conclusion This study demonstrates similar neutrophil and platelet engraftment in D-1 and D-2 melphalan cohorts with similar 2-year PFS and OS. Either D-2 or D-1 melphalan dosing schedule is safe and effective.